Analisis Pragmatik Bentuk Tuturan Deklaratif, Interogatif dan Imperatif dalam Surah al-Ahqaf - Susiani, Ika Wahyu (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
This study aims to reveal the pragmatic meaning contained in the declarative, interrogative, and imperative forms of speech in surah al-Ahqaf. This research is a kind of descriptive qualitative research with verse analysis technique based on pragmatic review using speech act theory. The results of this study indicate that the form of declarative speech in surah al-Ahqaf has the meaning of command (al-amr), determination (al-itsbat), denial (al-inkar), threats and promises (al-wa'id wa al-wa 'du), strengthening (al-ta'kid), frightening (al-tahdid or al-takhwif or al-tarhib), explaining the function (bayan al-faidah), giving good news (al-tabsyir), advice ( al-hatssu), threats (al-wa'id), reproaches (al-taubikh), warning against mistakes (tanbih ala al-khatha'), hoping for something that is difficult to achieve (al-tamanniy), scaring and threatening ( al-takhwif wa al-tahdid wa al-wa'id), warn and frighten (al-indzar wa al-takhwif), warn (al-tanbih or al-indzar) and encourage and encourage (al-targhib). While the interrogative form of speech means denial (al-inkar) and determination (al-itsbat) and imperative speech form means to weaken (al-ta'jiz), prayer (al-du'a'u), take lessons (al- i'tibar), challenge (al-tahaddu), insults and reproaches (al-ihanah wa al-taubikh) and confirmation (al-tatsbit).